Microbiological flora of cell phones: a reservoir of potential pathogens? - Sharma, Kanishtha; Kaur Najotra, Dipender; Slathia, Poonam; Raina, Shivani (International Journal of Medical Research and Review, 2017)
Background: Hospital associated infections are a major problem in all hospital settings. The heavy use of cell phones which come in close contact with the body surfaces could act as a fomite for microorganisms and it can transmit pathogenic as well as non pathogenic microorganisms. Objective: To determine the rate of bacterial contamination of cell phones of hospital staff and to study their antibiogram. Methods: A cross-sectional study was conducted in a tertiary care hospital. Sterile swabs were collected from cell phone surfaces of healthcare workers (HCW). The samples were processed as per standard microbiological techniques and antimicrobial susceptibility testing was done. Results: Out of the 100 cell phones studied, 60(60%) showed bacterial growth. 28(56%) were from doctors and 32(64%) from the paramedical staff. Staphylococcus aureus with 37(55.23%) isolates was predominant followed by CONS 12(17.93%), Pseudomonas sp. 7(10.44%), E. coli 4(5.97%) and Klebsiella pneumoniae 3(4.47%), 2(2.98%) Acinetobacter sp and Bacillus sp. 36 of HCW had cleaned their cell phones out of which 16 (44.44%) showed bacterial growth whereas 64 cell phones had never been cleaned, out of which 44 (68.75%) showed bacterial growth. Among the Gram positive isolates, Linezolid and Vancomycin were the most effective antibiotics and Imipenem and Piperacillin-Tazobactam were most effective against Gram negative isolates. Conclusion: HCW are exposed to pathogenic microorganisms which can be easily transferred to their cell phones thus acting as a source of infection to others. Cleaning of cellphones with alcohol based disinfectants and frequent hand washing should be encouraged.